Histopathological correlation of resected appendicectomy specimens - a five year study in a tertiary care centre in Kerala - Dr. Navya Narayanan O.; Dr. Siyad P.; Dr. Annu Elizabeth John (Tropical Journal of Pathology and Microbiology, 2019)
Background: Acute Appendicitis is one of the commoncause of acute abdomen leading to appendectomy which is one of the most frequently performed operations all over the world. Being a common surgery, appendicectomy specimens contribute a major part of routine specimens in any pathology laboratory. a large number of medical and surgical diseases can closely mimic appendicitis leading to negative appendicectomy.Objectives: To find out the age, sex related incidence anddifferent histopathological lesions seen in resected appendicectomy specimens in a tertiary care centre in south India. We also tried to find out negative appendicectomy rate.Materials and Method: This is a retrospective study conducted in the department of pathology, Sree Narayana Institute of Medical Sciences, Kerala. We analyzed the histopathology reports of thosepatients who had undergone appendicectomy in our hospitalduring last five year period (January 2014- December 2018).Result: During the study period of five years, 597 appendectomies were done. The mean age of the patients undergoing appendicectomy was found to be 25-35 years. Most of the patients were adults between 21-30 years and number of male patients (386) was more compared to females. Acute appendicectomy specimens showed the presence of fecoliths, gangrene, serositis, worms, lymphoidhyperplasia etc. The negative appendectomy rate was 5.6%.Conclusions: Detailed histopathological examination is always recommended in appendicectomy specimensnot only toconfirm thediagnosis,but also to rule outincidental pathologies their by leading tobetter patient outcome.